2007
DOI: 10.1007/s10665-007-9200-4
|View full text |Cite
|
Sign up to set email alerts
|

Trapping of water waves by moored bodies

Abstract: Certain types of floating bodies are known to support trapped modes, with oscillatory fluid motion near the body and no energy radiation in the far field. Previous work has considered either fixed bodies, where the boundary conditions are homogeneous, or bodies which are freely floating and moving without any exciting force. For a fixed body the existence of a trapped mode implies that there is no unique solution of the boundary-value problem for the velocity potential with a prescribed body motion. For a free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Porter and Evans [26] started with a pair of rectangular cylinders or a thick-walled cylindrical shell (in 2-and 3-dimensions respectively) and varied the geometry to find motion trapping structures. Motion-trapping structures with mooring restraints were studied by Evans and Porter [5], who found that a moored submerged circular cylinder moving in heave or sway could be a motion trapping structure, and Newman [25] who analysed mooring stiffnesses on the continuum from −∞ to ∞.…”
Section: Introductionmentioning
confidence: 99%
“…Porter and Evans [26] started with a pair of rectangular cylinders or a thick-walled cylindrical shell (in 2-and 3-dimensions respectively) and varied the geometry to find motion trapping structures. Motion-trapping structures with mooring restraints were studied by Evans and Porter [5], who found that a moored submerged circular cylinder moving in heave or sway could be a motion trapping structure, and Newman [25] who analysed mooring stiffnesses on the continuum from −∞ to ∞.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, ϕ m satisfies the same estimates at infinity as the remainder R in (13). Thus, any function ϕ m defined by formulae (18) and (19) with r = r m can serve as the first component of an eigensolution provided the vectors χ (k) * and the water domain W are chosen properly.…”
Section: Velocity Potentials Of Trapped Modesmentioning
confidence: 95%
“…No other rigorous results about this problem had been obtained until recently. However, after 2005 a number of authors considered the question of trapped modes at the heuristic level and various two-dimensional and axisymmetric trapping structures were proposed by virtue of numerical computations (see [13,14,3,19,20,21,4], which are listed in the chronological order). In most of these papers, a simplified model is treated; it deals with a freely floating body constrained to the heave motion only.…”
Section: Introductionmentioning
confidence: 99%
“…The right-hand side of equation 12is proportional to the hydrodynamic force on the structure due to the fluid oscillations. For a moored structure, the possibility of finite-energy motions that satisfy (11) and (12) with non-zero φ and V has been known for some time and there have been a number of recent developments (Evans & Porter 2007, Newman 2008. Non-trivial solutions with finite energy of equations (9)-(12) for structures without moorings are referred to as motion trapped modes and, for V = 0, their existence has been established using the inverse method by McIver & McIver (2006, and solutions for half-immersed circular cylinders have been found by Porter & Evans (2009).…”
Section: Formulationmentioning
confidence: 99%